2018
DOI: 10.1007/s42154-018-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

$$\hbox {CO}_{2}$$ CO 2 Reduction Request and Future High-Efficiency Zero-Emission Argon Power Cycle Engine

Abstract: To meet the requirements of strict fuel consumption and emission limits, continuously increasing the thermal efficiency of an internal combustion engine and decreasing its exhaust emissions are the main challenges to its sustainable development within the automotive industry. Considering the competition with other zero-emission powertrain systems, such as vehicle batteries and fuel cells, the development of the internal combustion engine needs to focus on producing higher efficiency and zero emissions to meet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Currently, owing to the high cost of He, most developments in inert gas cycle internal combustion engines are based on Ar. Existing research 32 has shown that hydrogen can achieve stable combustion in an Ar atmosphere, significantly improving engine thermal efficiency. Additionally, because N 2 was replaced, there was no NO x present in the combustion products, achieving truly clean combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, owing to the high cost of He, most developments in inert gas cycle internal combustion engines are based on Ar. Existing research 32 has shown that hydrogen can achieve stable combustion in an Ar atmosphere, significantly improving engine thermal efficiency. Additionally, because N 2 was replaced, there was no NO x present in the combustion products, achieving truly clean combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Argon Power Cycle (APC) is a novel power system for a higher efficiency and zero emissions [2]. In APC, the working substance is the argon (Ar), the oxide is oxygen, and the fuel is not limited.…”
Section: Introductionmentioning
confidence: 99%
“…The automobile power source is the key point of the continuous development of the automobile industry [4]. Good alternative fuels, such as biodiesel, alcohols and compressed natural gas (CNG), have solved some environmental problems, as well as some energy problems [5][6][7]. However, since the beginning of 2013, many places in China had hazy weather, which slowly spread to the surrounding areas from Beijing, Tianjin as well as Hebei.…”
Section: Introductionmentioning
confidence: 99%